Chemical compositions, antioxidant and antibacterial activities of kepel (Stelechocarpus burahol) fruit flesh and peel extracts - DEWI SUNDARI; DESI SUCI HANDAYANI; VENTY SURYANTI (Society for Indonesian Biodiversity, 2023)
Abstract. Sundari D, Handayani DS, Suryanti V. 2023. Chemical compositions, antioxidant and antibacterial activities of kepel (Stelechocarpus burahol) fruit flesh and peel extracts. Biodiversitas 24: 4668-4675. Kepel (Stelechocarpus burahol (Bl.) Hook f. & Th.) has been utilized by royalty in Java, Indonesia as perfume, deodorant and anti-agingagent. S. burahol fruit flesh has diuretic properties and can helpavoid kidney irritation. S. buraholpossesses anti-hyperuricemia and xanthine oxidase inhibitory properties, as well as antiseptic, anti-inflammatory, and antioxidant activity. Chemical contents and biological activities of S. burahol fruit and peel extracts were investigated in the present study. Based on GC-MS spectra, methanol fruits extract contains dodecanoic acid-1,2,3-propanetriyl ester. Methanol peel extract contains hexadecanoic acid methyl ester; 2,6,10,15,19,23-hexamethyl-2,6,10,14,18,22-tetracosahexaene and dodecanoic acid-1,2,3-propanetriyl ester. Ethyl acetate peel extract contains dodecanoic acid-1,2,3-propanetriyl ester. LC-MS analysis revealed that ethyl acetate fruit flesh extract contains pelargonidin-malonylrhamnoside (anthocyanins), 8-epiiridodial glucoside tetraacetate (isoprenoid), epigallocatechin gallate (catechin) and 5-octadecenal (fatty aldehydes). Ethyl acetate fruit peel extract contains 1,5-dicaffeoylquinic acid (flavonoid), 1,6-di-o-galloylglucose (tannins), luteolin 7-O-glucoside (cynaroside),methyl hemiacetal in 3,4-DHPEA-EA (iridoids). Methanol extract of fruit flesh has strong antioxidant activity, whereas three other extracts have very strong antioxidant activities. S. burahol peel extract inhibited the S. aureus growth at a concentration extract of 15,000 to 25,000 ppm. These antioxidant and antibacterial activities are associated with the chemical composition of S. burahol fruit flesh and peel extracts. Further research into other biological functions and in vivo investigations are required for future studies.